The Effect of Bay Leaf Juice (Syzygium Polyanthum (Wight)) on the Death of Aedes Aegypti Instar III Mosquito Larvae - Swandini, Fika Anjar; Nugrahani, Ardina; Prasetyowati, Alberta Tri (Journal of Social Science, 2024)
Dengue Hemorrhagic Fever (DHF) is an endemic disease which is a health problem in Indonesia, which can be transmitted through the bite of the Aedes aegypti mosquito . Control of the Aedes aegypti mosquito as a dengue vector has been widely carried out using synthetic controls, other controls can be carried out using natural larvicides . Bay leaves (Syzygium polyanthum (Wight)) are one of the plants that can be used as a natural larvicide because they contain alkaloids, flavonoids, phenolics, terpenoids, tannins, saponins and essential oils. This research aims to determine the effect of bay leaf juice on the death of third instar Aedes aegypti mosquito larvae. This research is an experimental study by looking at the death of third instar Aedes aegypti mosquito larvae from bay leaf juice. The treatment was carried out by making various concentrations of bay leaf juice, namely 4%, 8%, 16%, 20%, 32%, 64% and 80%. Each treatment container contained 25 third instar Aedes aegypti mosquito larvae with 2 repetitions for 24 hours. Data were analyzed using one way ANOVA analysis of variance. The conclusion of this research is that bay leaf juice has a significant effect on the death of third instar Aedes aegypti mosquito larvae and a concentration of 16% is an effective concentration in killing third instar Aedes aegypti mosquito larvae.